Evaluation of the incidence of ocular manifestations in HIV-infected pediatric patients: a cross-sectional study - Rekha KR (HIV & AIDS Review. International Journal of HIV-Related Problems)
Background Acquired immunodeficiency syndrome (AIDS) is a pandemic affecting about 1.8 million children aged 0-14 years globally (2019). Exposure to human immunodeficiency virus (HIV) occurs in utero, during delivery, and lactation. There is lack of knowledge and information regarding ocular manifestations in HIV-positive children. Aim of the paper was to determine the incidence of ocular manifestations and their correlation with CD4+ count level in HIV-positive children.